Determinants of Adoption of Climate-Smart Agriculture Practices among Farmers in Sheema District, Western Uganda - Benard Mugisha; David Agole; John C. Ewing; Cosmas Wacal; Eriya B. Kule (Journal of International Agricultural and Extension Education, 2025)
With the rapid pace of climate change and its impact on food security and livelihoods, Climate-Smart Agriculture (CSA) is one strategy aiming to help farmers adopt more sustainable farming practices. This study examines the determinants of adoption of CSA practices by farmers in Sheema District in Western Uganda. Through 228 household surveys, we examined the influence of socio-demographic and institutional factors on adoption of climate smart agriculture practices using the multivariate probit model. Most of the farmers are aware of the CSA practices and are utilizing some strategies but have little understanding of how each contribute to the three pillars of CSA. The multivariate probit model results show that the adoption of CSA practices is significantly associated with gender, age, household size, land size, household income, access to agricultural credit and membership to a social group. It recognizes that there is need to; i) tailor appropriate and site-specific CSA practices, and ii) critically analyze the challenges farmers face to have a better understanding of the necessary steps to take that will benefit them and facilitate adoption.
Keywords: Climate smart; smallholders; agriculture; adoption